Moving beyond anthropocentrism in leisure research: multispecies perspectives. Issue 2 (15th March 2019) - Dashper, Katherine
ABSTRACT: This commentary challenges the anthropocentrism of leisure research and raises some of the limitations of considering leisure solely from human-centric perspectives. Research from the emerging subfield of human-horse relationships is used to illustrate how more-than-human analyses can enrich understandings of leisure as multispecies practices, encounters and interactions. Embracing multispecies perspectives may open up new and challenging ethical, theoretical, methodological and practical issues for the field of leisure studies.